PERAN MODAL SOSIAL ORANG TUA DALAM KEPUTUSAN MENYEKOLAHKAN ANAK KE MADRASAH IBTIDAIYAH DI ERA PERSAINGAN SEKOLAH DASAR UMUM - chairil chairil; Kurniawati Dewi (Al-Azkiya: Jurnal Pendidikan MI/SD, 2026)
Abstract   This study aims to analyze the role of parental social capital in the decision to enroll children in Madrasah Ibtidaiyah amidst increasingly competitive rivalry with public primary schools. This research employs a qualitative approach through library research method by analyzing various relevant scientific literature sources. The findings reveal that three components of social capital, namely social networks, community trust, and social norms, collectively shape Muslim parents' preferences in choosing Madrasah Ibtidaiyah as their children's educational institution. The role of religious figures and community authority figures further reinforces this social capital dynamic significantly. This study concludes that strengthening Madrasah Ibtidaiyah requires not only improving academic quality, but must also be accompanied by strategic and sustainable management of social capital to maintain the trust and loyalty of the Muslim community toward Islamic educational institutions at the primary level. Keywords: Social Capital, Madrasah Ibtidaiyah, Educational Decision